Maternal mortality report (London : The Maternal Mortality Committee)
1934-10 1934 1930s 19 pages of childbirth, is more susceptible to puerperal infection, and runs a greater risk at her confinement. The unborn baby is also similarly affected." From Southampton it is reported that "owing to widespread poverty, the maternity services and grants of free milk and cod liver oil have had to be greatly increased." (The milk grant has been more than doubled.) "The increase of unemployment entails a diet which, while usually adequate in quantity, is often inadequate in quality." In view of such remarks as the above, such a step as the following, noted by the County Medical Officer for Monmouthshire, is especially to be deplored :— "In view of the serious financial position of the County it was ordered by the County Council early in the year that the Maternity and Child Welfare estimates should be reduced by the annual figure of £3,260. This year (1933-34) a saving of £637 is required in addition to the above figure of £3,260. To carry out this instruction it was found necessary to revise the scheme for the provision of milk for necessitous mothers and for infants, to ensure that the supply should be strictly limited to those who are in need on medical grounds." * Writing on this subject, the County Medical Officer for Salop says: "Milk is supplied free in necessitous cases and, before the necessary order is given, each case is carefully inquired into by the Medical Officer of the Centre and one of the lady helpers ; or where there is no Centre, by the Health Visitor and a local responsible person. The opinion of the Relieving Officers is obtained in all cases, and all the reports are carefully scrutinised at the central office. Notwithstanding this careful supervision there has been a gradual increase in the amount of free milk supplied, no doubt chiefly as a result of the prevailing industrial depression, which is bringing a larger number of families within the scope of the scheme. Although the sum of £1,659 was spent on free milk in the year ended March, 1933, it must be recognised that this is undoubtedly preventive work of great value, because, if a considerable proportion of the poorer people go short of important articles of diet, as seems probable, the provision of milk should greatly improve the health of the children, lessen the amount of rickets, and diminish the number of infectious illnesses which are so frequently associated with this condition." In concluding our analysis, one cannot but agree with the County Medical Officer for Monmouthshire that "to reduce the efficiency of the Maternity and Child Welfare Service would be false economy, for what is being done now for the infant is for the benefit of the next generation." *We also note that in this County a grant of £350 to the Monmouthshire Nursing Association to provide Midwifery scholarships was terminated by the County Education Committee. (15) 292/824/1/20